Development of a Framework for Assessing the Degree of Course and Program Outcome Attainment utilizing Outcome-Based Education Framework - Biswal, Dillip Kumar; Moharana, Bikash Ranjan; Muduli, Kamalakanta (Journal of Engineering Education Transformations, 2025)
Outcome-based education (OBE) has been widely adopted in technical universities due to its advantages such as providing students with clear expectations, offering flexibility in lesson plan layout, facilitating comparison for improvement, and promoting student engagement in the classroom. Assessing the degree and quality of program learning abilities obtained by students using various assessment methods is a crucial component of OBE. This study presents an assessment approach for evaluating the achievement of course outcomes (CO) and program outcomes (PO) among engineering graduates, in accordance with the guidelines outlined by the National Board of Accreditation (NBA). This research is based on analysis of the data derived from students' internal and final examination scores. The achievements are condensed and data is generated, followed by a comparative analysis that can be utilized for the ongoing enhancement of student quality. Exploring indirect instruments such as graduate exit surveys, course end surveys, alumni surveys, and employer surveys has the potential to improve the assessment procedures for COs, POs, and Program Specific Outcomes (PSOs).